Growth and mineralogy in dental plates of the holocephalan Harriotta raleighana (Chondrichthyes): novel dentine and conserved patterning combine to create a unique chondrichthyan dentition - Meredith Smith, Moya (Zoological Lett, 2019)
ABSTRACT: The dentition in extant holocephalans (Chondrichthyes) comprises three pairs of continuously growing dental plates, rather than the separate teeth characterizing elasmobranchs. We investigated how different types of dentine in these plates, including hypermineralized dentine, are arranged, and how this is renewed aborally, in adult and juvenile dentitions of Harriotta raleighana (Rhinochimeridae). Individual plates were analysed using x-ray computed tomography (μCT), scanning electron microscopy (SEM) in back scattered mode with energy dispersive X-ray (EDX) analysis, and optical microscopy on hard tissue sections. RESULTS: Harriotta dental plates are made entirely of dentine tissue, mostly as trabecular dentine, bone itself being absent. Hypermineralized dentine forms in restricted ovoid and tritor spaces within trabecular dentine, inside a shell of outer and inner dentine layers. Trabecular dentine is ubiquitous but changes to sclerotic osteodentine near the oral surface by increasing density, remaining less mineralized than the hypermineralized dentine. All structures are renewed aborally, within a vascular dental pulp, a tissue suggested to be a source of stem cells for tissue renewal. Ca density profiles and concentrations of Mg, P, and Ca ions reveal extreme differences in the level and type of mineralization. Early mineralization in ovoids and tritors has very high levels of Mg, then a sudden increase in mineralization to a high total mineral content, whereas there is gradual change in trabecular dentine, remaining at a low level. Hypermineralized dentine fills the prepatterned ovoid, rod and tritor spaces, early at the aboral surface within the trabecular dentine. Deposition of the hypermineralized dentine (HD, proposed as new specific name, whitlockin replacing pleromin) is from surfaces that are lined with large specialized odontoblasts, (whitloblasts, instead of pleromoblasts) within cell body spaces connecting with extensive, ramifying tubules. Early mineralization occurs amongst this maze of tubules that penetrate far into the dentine, expanding into a mass of saccules and membranous bodies, dominating in the absence of other organic matrix. This early stage has hydroxyapatite, also significantly rich in Mg, initiated as a poorly crystalline phase. In the hypermineralized dentine, formation occurs as clusters of variably shaped crystals, arising from a sudden phase transition. CONCLUSIONS: In the hypermineralized dentine, high MgO + CaO + P(2)O(5) suggests that almost pure Mg containing tricalciumphosphate (MgTCP: (ß-Ca(3)(PO(4))(2)) (whitlockite) is present, with little or no hydroxyapatite. Serial replacement of tritors and ovoids is suggested to occur within the dental plate, probably representing a relic of patterning, as classically found in elasmobranch dentitions.